Measuring the food access dimension of food security: A critical review and mapping of indicators - Leroy, Jef L.; Ruel, Marie T.; Frongillo, Edward A.; Harris, Jody; Ballard, Terri J. (SAGE Publications, 2015)
With food security now a top priority for many governments and for the global development community, there is heightened awareness of the need to improve our understanding and measurement of food security.To bring clarity in the assessment of the food access dimension of food security at the household and individual level.For the most commonly used indicators, we reviewed their original purpose and construction, at what levels (household or individual) they were designed to be used, what components (quality, quantity, safety, and cultural acceptability) they were intended to reflect, and whether or not they have been tested for validity and comparability across contexts.We identified nine indicators and grouped them in three broad categories: experience-based, coping strategies, and dietary diversity. The indicators only capture the quantity and quality components of food access; none of the indicators capture information on safety or cultural acceptability of food access. Household Dietary Diversity (HDDS) and Food Consumption Score (FCS) are often considered indicators of both quantity and quality, but they have not been validated for the latter.We recommend the use of experience-based indicators, HDDS, or FCS to assess household access to energy; experience-based indicators to assess household access to diet quality (defined qualitatively as not having to adopt practices that favor acquiring cheaper, less appealing, and less micronutrient-dense foods); and individual dietary diversity scores for women or children to assess individual access to diet quality, defined as micronutrient adequacy.